5(2-x)-3(4-2r)=20

Simple and best practice solution for 5(2-x)-3(4-2r)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2-x)-3(4-2r)=20 equation:


Simplifying
5(2 + -1x) + -3(4 + -2r) = 20
(2 * 5 + -1x * 5) + -3(4 + -2r) = 20
(10 + -5x) + -3(4 + -2r) = 20
10 + -5x + (4 * -3 + -2r * -3) = 20
10 + -5x + (-12 + 6r) = 20

Reorder the terms:
10 + -12 + 6r + -5x = 20

Combine like terms: 10 + -12 = -2
-2 + 6r + -5x = 20

Solving
-2 + 6r + -5x = 20

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 6r + 2 + -5x = 20 + 2

Reorder the terms:
-2 + 2 + 6r + -5x = 20 + 2

Combine like terms: -2 + 2 = 0
0 + 6r + -5x = 20 + 2
6r + -5x = 20 + 2

Combine like terms: 20 + 2 = 22
6r + -5x = 22

Add '5x' to each side of the equation.
6r + -5x + 5x = 22 + 5x

Combine like terms: -5x + 5x = 0
6r + 0 = 22 + 5x
6r = 22 + 5x

Divide each side by '6'.
r = 3.666666667 + 0.8333333333x

Simplifying
r = 3.666666667 + 0.8333333333x

See similar equations:

| 2b+3=b+19 | | 15x^3+3x= | | 3l-6+2l=-2+l | | 6i/5+3i= | | [2x-2]=6 | | 5y=7x+2 | | 189=9-9x | | -(0.79k+0.227)=-(2.09k+0.838) | | 6/4+6i= | | p^3(e^5p-7)-(6p/2_p^2) | | lnx+2=7+lnx-1 | | lnx^3=7lnx | | 5/7×3/4=? | | 4i/8+2i= | | -2x+2=5y | | (2x-1/3)^2 | | 1/3(9h*h-6h) | | 9x/2-10x=7 | | 3(2x+1)+4=24 | | 7x^2-48x+7=0 | | 1/2-1/8=? | | 17-p=7p-13 | | 2x^5-18x^3-2x^2+18=0 | | ln(x+2)=7+ln(x-1) | | 5/12=K-1/3 | | 3n-8(8-8n)=338 | | 3p=-2/3 | | 500=300x+200 | | y=4x^2+24-7 | | 4tan^2x-3=1 | | 6x+3=2x | | 2-(7x+15)=13-3x |

Equations solver categories